2020
DOI: 10.3390/ijerph17145226
|View full text |Cite
|
Sign up to set email alerts
|

Factors Affecting Arsenic Methylation in Contaminated Italian Areas

Abstract: Chronic arsenic (As) exposure is a critical public health issue. The As metabolism can be influenced by many factors. The objective of this study is to verify if these factors influence As metabolism in four Italian areas affected by As pollution. Descriptive analyses were conducted on 271 subjects aged 20–49 in order to assess the effect of each factor considered on As methylation. Percentages of metabolites of As in urine, primary and secondary methylation indexes were calculated as indicators for metabolic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 106 publications
(133 reference statements)
0
3
0
Order By: Relevance
“…Proteins related to THF metabolism ( Figure 2 ) and also proteins involved in the synthesis of chorismate, a precursor of p-aminobenzoate, were induced in the presence of As(III), suggesting a relationship between THF metabolism and arsenic resistance. It has been shown that the administration of folic acid reduces arsenic toxicity in humans [ 56 ], and this effect could be due to the requirement of THF for arsenic methylation, either directly or allowing the synthesis and recycling of SAM, which is required for ArsM-type methyltransferases [ 57 , 58 ]. In addition, the enzyme GAPDH catalyzes the formation of arseno-phosphoglycerate, which is exported by the permease ArsJ [ 30 , 31 ].…”
Section: Resultsmentioning
confidence: 99%
“…Proteins related to THF metabolism ( Figure 2 ) and also proteins involved in the synthesis of chorismate, a precursor of p-aminobenzoate, were induced in the presence of As(III), suggesting a relationship between THF metabolism and arsenic resistance. It has been shown that the administration of folic acid reduces arsenic toxicity in humans [ 56 ], and this effect could be due to the requirement of THF for arsenic methylation, either directly or allowing the synthesis and recycling of SAM, which is required for ArsM-type methyltransferases [ 57 , 58 ]. In addition, the enzyme GAPDH catalyzes the formation of arseno-phosphoglycerate, which is exported by the permease ArsJ [ 30 , 31 ].…”
Section: Resultsmentioning
confidence: 99%
“…Some arsenic-containing composites are also utilized in the production of optics and microelectronics [ 45 ]. Sodium arsenite has frequently been applied as a herbicide and nonselective soil sterilant [ 46 ].…”
Section: Means Of Human Arsenic Exposurementioning
confidence: 99%
“…Betaine is derived from choline, and choline synthesis is upregulated by estrogen ( Resseguie et al, 2007 ). Since adipose tissue is estrogenic ( Kershaw and Flier, 2004 ), Abuawad et al have proposed the causal pathway adiposity → estrogen → choline → arsenic methylation ( Abuawad et al, 2021 ; Bustaffa et al, 2020 ). They cautioned, however, that choline may promote adiposity ( Zeisel, 2013 ), and temporality among adiposity, choline, and arsenic methylation remains unclear ( Abuawad et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%